Integrated Analysis of Transcriptome mRNA and miRNA Profiles Reveals Self-Protective Mechanism of Bovine MECs Induced by LPS - Chen, Ling; Liu, Xiaolin; Li, Zhixiong; Wang, Jian; Tian, Rongfu; Zhang, Huilin (Frontiers in Veterinary Science, 2022)
Many studies have investigated the molecular crosstalk between mastitis-pathogens and cows by either miRNA or mRNA profiles. Here, we employed both miRNA and mRNA profiles to understand the mechanisms of bovine mammary epithelial cells (bMECs) response to LPS by RNA-Seq. The total expression level of miRNAs increased while mRNA reduced after LPS treatment. 41 differentially expressed mRNAs and 45 differentially expressed miRNAs involved in inflammation were screened out. We found the NFκB-dependent chemokine CXCL1, CXCL3, CXCL6, IL8 and CX3CL1 are early and strongly induced. The anti-apoptosis was active because BCL2A1 and BIRC3 significantly increased with a higher expression. The effects of anti-microbe and inflammation were weakly activated because TNF, IL1, CCL20, CFB, S100A, MMP9 and NOS2A significantly increased but with a low expression, IL6 and β-defensin even decreased. These activities were supervised by the NFKBIA to avoid excessive damage for bMECs. bta-let-7a-5p, bta-miR-30a-5p, bta-miR-125b and bta-miR-100 were essential to regulate infection process in bMECs after LPS induction. Moreover, lactation potential of bMECs was undermined because of significantly downregulated SOSTDC1, WNT7B, MSX1 and bta-miR-2425-5p. Summarily, bMECs may be not good at going head-to-head with the pathogens, they seem to be mainly charged with sending out signals for help, and anti-apoptosis for maintaining lives after LPS induction.